Sultan II.Abdülhamid döneminde maliye komisyonları ve faaliyetleri (1876-1909) - Bölükbaşı, Ömerül Faruk (My University, 2003)
unknown
Keywords: Ekonomi; Finansman ekonomisi; Maliye_Türkiye_Osmanlı Imparatorluğu